Pemanfaatan Data untuk Pembuatan Kebijakan dalam Penanggulangan Penggangguran di Kota Bandung Melalui Aplikasi Bandung Integrated Manpower Management Application (BIMMA) - Agustian Nugraha; Khaerul Umam; Siti Alia (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
Unemployment is one of the issues confronting Indonesia in the labor market. This is due to a lack of jobs, inflation, explosions, or a lack of investment, all of which lead the unemployment rate to rise, particularly in the city of Bandung. As a result, the Bandung City Manpower Service developed the BIMMA application, one of which is to serve as a forum for connecting companies and job seekers in online job fairs in order to reduce unemployment. The purpose of this study is to describe the policies taken by the Bandung City Manpower Service in dealing with numbers in the city of Bandung based on data included in the BIMMA application. Descriptive research using a qualitative approach is used in this study. Following that, data was gathered through structured and semi-structured interviews, observation, documentation, and library research. Data analysis employs a pattern approach from the bottom up in a hierarchical approach, with data triangulation serving as the validity test. According to the findings of the study, the data obtained from the BIMMA application is used as statistical data for reports to local governments and as an indicator or reference for the agency to create work programs the following year in the form of open training or apprenticeship through competency tests on applications that are used to reduce unemployment in Bandung City.Keywords: Job Fair, E-government, unemployment